Exploring Mycorrhizal Associations in Orchids: Isolation, Identification, and Morphological Insights - Bhattacharjee, Saptaparna; Attri, Lucky K (Asian Journal of Biological and Life Sciences, 2025)
Background/Purpose: Epiphytic orchids, such as Aerides odorata L., rely on symbiotic mycorrhizal fungi for nutrient acquisition, germination, and early growth due to the nutrient-deficient nature of their seeds. The hypothesis of this study was that Rhizoctonia spp. are the primary mycorrhizal fungi associated with A. odorata and that their growth characteristics vary depending on the culture medium. Materials and Methods: To test this, fungal samples were isolated from A. odorata and cultured on four different media: Potato Dextrose Agar (PDA), Sabouraud Dextrose Agar (SDA), Malt Extract Agar (MEA), and Czapek Dox Agar (CZA). Results: Microscopic examination confirmed the presence of Rhizoctonia spp., characterized by septate hyphae and the absence of conidia, indicating asexual reproduction. Fungal growth was evaluated, with PDA and SDA showing the most rapid and extensive growth, while CZA exhibited the slowest and most restricted growth. Conclusion: The results suggest that Rhizoctonia spp. play a significant role in the symbiosis of A. odorata, and that media selection is crucial for optimizing fungal cultivation. These findings contribute to improving ex situ fungal culture techniques, which are vital for the conservation and sustainable propagation of A. odorata L.
Keywords: Aerides odorata L.; Culture media; Fungal proliferation; Mycorrhizal Fungi; Rhizoctonia spp.